Disordered Eating in a Digital Age: Eating Behaviors, Health, and Quality of Life in Users of Websites With Pro-Eating Disorder Content - Peebles, Rebecka; Wilson, Jenny L; Litt, Iris F; Hardy, Kristina K; Lock, James D; Mann, Julia R; Borzekowski, Dina LG (JMIR Publications, 2012)
BackgroundMuch concern has been raised over pro-eating disorder (pro-ED) website communities, but little quantitative research has been conducted on these websites and their users. ObjectiveTo examine associations between levels of pro-ED website usage, disordered eating behaviors, and quality of life. MethodsWe conducted a cross-sectional, Internet-based survey of adult pro-ED website users. Main outcomes were Eating Disorder Examination Questionnaire (EDE-Q) and Eating Disorder Quality of Life (EDQOL) scores. ResultsWe included responses from 1291 participants; 1254 (97.13%) participants were female. Participants had an average age of 22.0 years and a mean body mass index of 22.1 kg/m2; 24.83% (296/1192) were underweight; 20.89% (249/1192) were overweight or obese. Over 70% of participants had purged, binged, or used laxatives to control their weight; only 12.91% (163/1263) were in treatment. Mean EDE-Q scores were above the 90th percentile and mean EDQOL scores were in the severely impaired range. When compared with moderate and light usage, heavy pro-ED website usage was associated with higher EDE-Q global (4.89 vs 4.56 for medium and 4.0 for light usage, P < .001) and EDQOL total scores (1.64 vs 1.45 for medium and 1.25 for light usage, P < .001), and more extreme weight loss behaviors and harmful post-website usage activities. In a multivariate model, the level of pro-ED website usage remained a significant predictor of EDE-Q scores. ConclusionsPro-ED website visitors reported many disordered eating behaviors, although few had been treated. Heavy users reported poorer quality of life and more disordered eating behaviors.